Pengembangan Model Pembelajaran Berbasis Multimedia Untuk Meningkatkan Efektivitas Kemampuan Membaca Mahasiswa - Endang Sulistianingsih (Universitas Pancasakti Tegal, 2018)
The aimed of this study was to test learning model development based multimedia to improve the effectiveness of students’ reading comprehension, this issue was crucial due to the improvement of students’ reading comprehension would help students achievement follow the development of the world in the field of science and technology, considering that most scientific works in the field of science and technology were released in English. The participants of this study were students of the English Language Education program. This study used a true experimental research design with pre-test post-test one group design, with stages covering preparation, implementation, and reporting. The result of the study is that the multimedia-based learning model is effective for improving students' reading comprehension.